Educational Preparation and Course Approach of Undergraduate Sports Nutrition instructors in Large U.S. Institutions - Kayla Marie Norton; Randall Spencer Davies; James Derek LeCheminant; Susan Fullmer (MDPI AG, 2023)
College courses are often offered from various disciplines, and depending on which department offers the class, the course could be taught by faculty with different educational preparation or training. This could result in significant differences in the approach and content of the course (i.e., theoretical or applied) or a difference in the instructors' perceived importance and, therefore, the depth and time spent on various topics. We evaluated potential differences in the sports nutrition curriculum because it is a course that is usually taught by either nutritionists or exercise physiologists. A cross-sectional survey was sent to sports nutrition instructors at accredited large U.S. institutions. Descriptive statistics were analyzed via an ANOVA and Χ2 using Crosstabs in Qualtrics. Alpha was set at p < 0.001. Additionally, short interviews with some participants were recorded and transcribed verbatim. The findings of this study indicated that regardless of the instructor's educational preparation and discipline, the majority of sports nutrition topics received similar time and depth and were rated as similarly important (p > 0.001). Out of 10 current textbooks, the majority of instructors preferred only 1 of 4 of them. From the short interviews, instructors reported that their courses were more applied than theoretical or balanced between the two. Most instructors designed their courses with a focus on achieving applied outcomes.